μ-opioid receptor agonists and psychedelics: pharmacological opportunities and challenges - Salinsky, Leah M.; Merritt, Christina R.; Zamora, Joshua C.; Giacomini, Juliana L.; Anastasio, Noelle C.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2023)
Opioid-involved overdose deaths are a massive public health problem involving the intertwined misuse of prescription opioids for pain management with the emergence of potent fentanyl derivatives, sold as standalone products/adulterants in counterfeit prescription opioids or heroin. The incidence of repeated opioid overdose events indicates problematic use patterns consistent with the development of the medical condition of opioid use disorder (OUD). Prescription and illicit opioids reduce pain perception by activating µ-opioid receptors (MOR) localized to the CNS. Dysregulation of meso-corticolimbic circuitry that subserves reward and adaptive behaviors is involved in the progressive behavioral changes that promote and are consequent to OUD. Although opioid-induced analgesia and rewarding effects of abused opioids are primarily mediated through MOR activation, serotonin is an important contributor to the pharmacology of opioid abused drugs and OUD. There is a recent resurgence of interest into psychedelic compounds that act primarily through the 5-HT2A receptor (5-HT2AR) as a new frontier in combatting such diseases (e.g., depression, anxiety, and OUD). Emerging data suggest that the MOR and 5-HT2AR crosstalk at the cellular level and within nodes of OUD circuitry, highlighting a major opportunity for novel pharmacological intervention for OUD. There is a gap in the preclinical profiling of psychedelic 5-HT2AR agonists in OUD models. Further, as these molecules carry risks, additional analyses of the profiles of non-hallucinogenic 5-HT2AR agonists and/or 5-HT2AR positive allosteric modulators may provide a new pathway for 5-HT2AR therapeutics. In this review, we discuss the opportunities and challenges associated with utilizing 5-HT2AR agonists as therapeutics for OUD.